Bayesian Monitoring. - Roland Kirstein (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 2005)
This paper presents a modification of the inspection game: The ?Bayesian Monitoring? model rests on the assumption that judges are interested in enforcing compliant behavior and making correct decisions. They may base their judgements on an informative but imperfect signal which can be generated costlessly. In the original inspection game, monitoring is costly and generates a perfectly informative signal. While the inspection game has only one mixed strategy equilibrium, three Perfect Bayesian Equilibria exist in my model (one in pure strategies, two in mixed). These outcomes can be described with respect to their punishment styles: tyrannic, draconian, and lenient. The Bayesian Monitoring model, just as the inspection game, has different implications than enforcement models in the tradition of Becker (1968). Total deterrence of bad behavior is impossible, and the equilibrium probability of good behavior is independent of the suspect?s own payoff parameters. Hence, the maximum fine result does not apply. – – Dieses Paper präsentiert eine Modifikation des "Inspection Game". Bayesian Monitoring basiert auf der Annahme, daß Richter ein Interesse an korrekten Urteilen haben. Sie können ihr Urteil auf ein kostenlos verfügbares, aber imperfektes Signal stützen. Im "Inspection Game" ist Monitoring perfekt, wirft jedoch Kosten auf. Das Inspektion Game weist lediglich ein Gleichgewicht in gemischten Strategien auf, wohingegen es im Bayesian Monitoring Game drei Gleichgewichte gibt: eines in reinen, zwei in gemischten Strategien. Diese Gleichgewichte unterscheiden sich hinsichtlich des Bestrafungs-Stils: tyrannisch, drakonisch, freundlich. Wie das Inspektion Game führt Bayesian Monitoring zu anderen Ergebnissen als Rechtsdurchsetzungsmodelle in der Tradition von Becker (1968). Insbesondere gilt das "Maximum Fine"-Ergebnis nicht.
Keywords: D81; C72; K40; 330; Imperfect Decision-Making; Perfect Bayesian Equilibrium; Enforcement; Maximum Fine Result